Thoracic metastasectomy for nonseminomatous germ cell tumors - Pfannschmidt, Joachim; Hoffmann, Hans; Dienemann, Hendrik (Journal of thoracic oncology, 2010)
Pulmonary metastases are common in patients after resection for nonseminomatous germ cell tumor of the testis. There is solid evidence that resection for residual pulmonary disease, after adjuvant chemotherapy, can provide patients with a long-term survival. This article addresses the issues of patient selection and prognostic factors with the current review of pulmonary metastasectomy in metastatic nonseminomatous germ cell tumors retrieved from retrospective studies. In summary, there is a substantial body of evidence demonstrating that resection of residual lesions after chemotherapy can be performed safely with a low mortality rate. For a subset of patients with viable malignant tumor cells after chemotherapy, the overall results of a 5-year actuarial survival rate ranged between 42 and 61%. However, no presurgical algorithm had proven effective at predicting histologic outcome and, similar to that in pulmonary metastasectomy in general, no prospective randomized trials have been conducted to define the role of surgery versus a nonsurgical treatment regimen.